Research on Ecological Environment Issues and Ecological Restoration in Mining Areas - Qin, Jie (International Journal of Natural Resources and Environmental Studies, 2025)
A comprehensive exploration was conducted on the ecological challenges faced by the three major environmental elements of the mining area ecosystem-soil, water, and atmosphere, and ecological restoration strategies were systematically elaborated to address these issues. In the field of land, reclamation and vegetation reconstruction technologies have been implemented; Ecological restoration and resource utilization measures have been taken for the water area. During the mining process in the mining area, subsidence prevention and control technologies including full filling mining, strip mining, and filling of overlying rock separation zones were adopted. At the same time, for the prevention and treatment of ground subsidence and cracks, a variety of technical means such as monitoring and early warning, temporary engineering reinforcement, anti-seepage treatment, vegetation reconstruction, and drainage ditch excavation have been comprehensively applied.